Inherited thrombophilia and anticoagulant therapy for women with reproductive failure. (25th November 2020) - Han, Ae Ra; Han, Jae Won; Lee, Sung Ki
Abstract: Reproductive failure (RF) is the inability to conceive or to carry a pregnancy to term, and its prevalence is not negligible. Pregnancy is a prothrombotic condition, which can be abnormally exaggerated in women with thrombophilia. Antiphospholipid syndrome is a cause of RF and effectively managed with heparin and aspirin. However, there are yet insufficient data in patients with RF and inherited thrombophilia. This review focuses on the significance of inherited thrombophilia and RF and the role of anticoagulants in pregnancy outcomes. A few randomized case‐control studies have investigated the effect of anticoagulation in RF with thrombophilia, and the results are yet debatable. Some inherited thrombophilia including mutations of factor V Leiden, prothrombin, and methylenetetrahydrofolate reductase and protein S deficiency are associated with RF and/or late pregnancy complications. There are several implications which influence the diagnosis and treatment. First, there is a lack of studies revealing appropriate thrombophilia markers and its cutoff values for RF specifically. Second, some thrombophilia markers change with sex and age. Lastly, the study designs of previous studies are heterogeneous in selecting the thrombophilia markers and drugs. Further studies to find adequate thrombophilia markers of RF are warranted and eventually elucidate the subgroups beneficial to anticoagulation treatment.